2019
DOI: 10.1002/cite.201800190
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of the Impact of Particle Friction on Bed Voidage in Fixed‐Beds

Abstract: The impact of the static friction coefficient, the initial particle orientation, and the particle height-to-diameter ratio on the bed voidage of random packings with a low tube-to-particle diameter ratio is investigated for spherical and cylindrical particles using the discrete element method. Based on the numerical results a correlation is proposed to predict the bed voidage as a function of the static friction coefficient and the tube-to-particle diameter ratio for spheres, equilateral and non-equilateral cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 13 publications
2
15
0
Order By: Relevance
“…This may indicate that an existing calibration curve, to some extent, can also be used if particle geometry is slightly modified, for example, small changes in aspect ratio. This is in accordance with results of Jurtz et al who found for cylindrical particles only little effect of aspect ratio on bed voidage if 0.5 < h / d p < 2. Nevertheless, further experimental and numerical investigations are needed to assess the validity and accuracy when using a calibration curve for modified particle shapes, especially for those with additional outer surface structure.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…This may indicate that an existing calibration curve, to some extent, can also be used if particle geometry is slightly modified, for example, small changes in aspect ratio. This is in accordance with results of Jurtz et al who found for cylindrical particles only little effect of aspect ratio on bed voidage if 0.5 < h / d p < 2. Nevertheless, further experimental and numerical investigations are needed to assess the validity and accuracy when using a calibration curve for modified particle shapes, especially for those with additional outer surface structure.…”
Section: Discussionsupporting
confidence: 90%
“…It was recently shown by Jurtz et al that the effect of tamping and surface characteristics can be lumped into the static friction coefficient and that it is possible to generate packings with a desired bed voidage by using an adapted friction coefficient. Nevertheless, their investigations were limited to simple particle shapes as cylinders, hollow‐cylinders and spheres, and the question remained if a once calibrated friction factor can be used to predictively describe the bed voidage of other reactor configuration with the same type of particles.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations